Math

Simplify the difference quotient
[f(2 + h) − f(2)]/h if h ≠ 0.

f(x) = x^2 − 3x

I keep getting the answer wrong...please help.

  1. 👍 0
  2. 👎 0
  3. 👁 123
  1. [f(2 + h) − f(2)]/h if h ≠ 0

    if f(x) = x^2 - 3x
    f(2+h) = 4+4h+h^2 - 3(2+h)
    = h^2 + h - 2
    f(2) = 4-6 = -2

    [f(2 + h) − f(2)]/h if h ≠ 0.
    = (h^2 + h - 2 - (-2))/h
    = (h^2 + h)/h
    = h + 1

    1. 👍 0
    2. 👎 0
    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra II

    Find the difference quotient for the following Rational Function f(x)=5/x using the four steps outlined below. a. find f(x+h) b. find f(x) c. substitute f(x+h) and f(x) into the difference quotient formula. d. simplify

    asked by Monique on June 23, 2014
  2. MATH

    Find and simplify the difference quotient for the given function. f(x)= -x^2+2x-1 I need to know how to set up the equations and simplify everything when dividing by h at the end.

    asked by Brian on June 3, 2018
  3. math

    simplify the difference quotient: f(x+h)-f(x), (h ≠ 0) as much as possible when f(x)=5x^2+4x+6

    asked by Liz on August 14, 2011
  4. Algebra

    Please Find the difference quotient f(x+h)-fx/h for f(x)= 4x-9 and simplify

    asked by Bonnie on June 22, 2009
  5. Algebra

    Find the difference quotient: f(x+h)-f(x)/h for f(x) = 4x-9 and simplify.

    asked by Kate on June 17, 2009
  6. math

    f(x)=4-x^2 simplify completly. Use difference quotient.

    asked by kori on January 2, 2013
  7. maths

    for the function f(x)= 3/(2x-1), determine the difference quotient and simplify

    asked by Anonymous on February 3, 2017
  8. maths

    for the function f(x)=3/(2x-1), determine the difference quotient and simplify

    asked by Toluwani on February 2, 2017
  9. precalculus

    Write and simplify the difference quotient for the function b(t)= 3t^2-4t+5 over the interval [7,7+h]

    asked by katrina on April 13, 2011
  10. Algebra

    My problem is compute and simplify the difference quotient f(x+h)-f(x)/h h is not = 0 f(x)=7x-9 answer is 7

    asked by Bradley on March 28, 2008

More Similar Questions